URGENSI HIKMAH DALAM PERGERAKAN DAKWAH DI QUR’AN SURAT AN-NAHL AYAT 125 - Nisa Amci Ilzania; Sunardi Bashri Iman (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
At this point, the perpetrators of terrorism and radicalism have entered the Muslim community, making it harder to preach. Therefore, a moderate narrative is necessary, and the method of the narrative with wisdom is the answer, as mentioned in the An-Nahl verse 125.